How do strategic networks help SMEs upgrade in global value chains? A cross-national analysis - Sangmin Kang; Changju Kim (Cogent Business & Management, 2023)
This study investigates whether strategic networks in global value chains affect the upgrade of suppliers and describes alternative ways of overcoming the barriers to such upgrades. Using a cross-national analysis, we examine the complex upgrade process for suppliers from a long-term perspective by applying qualitative research. We conduct semi-structured interviews to survey small and medium-sized enterprises in Japan and South Korea. The results show that suppliers in global value chains maintain long-term cooperative relationships with lead firms and utilize strategic networks to supplement the management capabilities required for strategic goals. Our findings also indicate that strategic multi-partner networks play a crucial role in ameliorating major barriers to upgrading. This study proposes that suppliers can upgrade through alternative methods utilizing strategic networks. Our findings thus generate important implications for managers working for suppliers in current or potential global value chains.
Keywords: 650; global value chain; Japan; small and medium-sized enterprises; South Korea; strategic network; upgrades